2020
DOI: 10.1002/jmri.27424
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Analysis Based on Multiparametric MRI for Predicting Early Recurrence in Hepatocellular Carcinoma After Partial Hepatectomy

Abstract: Background Preoperative prediction of early recurrence (ER) of hepatocellular carcinoma (HCC) plays a critical role in individualized risk stratification and further treatment guidance. Purpose To investigate the role of radiomics analysis based on multiparametric MRI (mpMRI) for predicting ER in HCC after partial hepatectomy. Study Type Retrospective. Population In all, 113 HCC patients (ER, n = 58 vs. non‐ER, n = 55), divided into training (n = 78) and validation (n = 35) cohorts. Field Strength/Sequence 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 39 publications
5
32
0
Order By: Relevance
“…Whereas, late recurrence is often attributed to the development of a de novo tumor which is different from the original tumor (4,10). Our results confirmed findings of other studies (6,10,11) that MVI and tumor size are independent factor for early recurrence. MVI is the single parameter enrolled by multiple models (25)(26)(27).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Whereas, late recurrence is often attributed to the development of a de novo tumor which is different from the original tumor (4,10). Our results confirmed findings of other studies (6,10,11) that MVI and tumor size are independent factor for early recurrence. MVI is the single parameter enrolled by multiple models (25)(26)(27).…”
Section: Discussionsupporting
confidence: 90%
“…Some studies (4,(6)(7)(8)(9) investigated and compared the difference between prognostic factors of two types of recurrence, it was found that early and late recurrences were associated with different predictive factors. The predictors of early recurrence are chiefly related to primary tumor and treatment, in particular, microvascular invasion (MVI) is regarded as a critical independent risk factor of early recurrence and poor prognosis after surgery treatments of HCC (8,10,11). For the late recurrence, there were no clinicopathological variables that were statistically associated with recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other radiomics analyses, the sample size is limited in our study. This difficulty is not uncommon in radiomics studies, and small datasets still demonstrate the potentials of radiomics approaches [ 57 60 ]. Our study initially indicates that radiomics analysis has potentials in predicting DD and LNM of ECC with promising performance.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the ability to preoperatively identify these high-risk patients will guide surgical management, postoperative monitoring, and treatment intervention (127,128). The radiomic model based on preoperative MRI can be used as a new tool to predict early relapse (18,19,(129)(130)(131)(132)(133)(134), relapsefree survival (135) and overall survival (OS) (136,137)…”
Section: Prediction Of Relapse and Prognosis After Surgical Resectionmentioning
confidence: 99%